Nitric oxide modulates folate-mediated one-carbon metabolism and mitochondrial energy levels of peaches during cold storage - Yang, Zhifeng; Zhu, Shuhua; Wang, Xiaoyu; Chen, Changbao; Huang, Dandan; Feng, Jianrong (Frontiers in Nutrition, 2023)
Folate-mediated one-carbon metabolism (FOCM) is closely associated with postharvest preservation. This study investigated the effects of exogenous nitric oxide (NO) on FOCM, storage quality, energy metabolism, and mitochondrial membrane integrity in cold-storage peach fruit. In this experiment, peaches were soaked with 1.5 mmol L−1S-nitrosoglutathione (GSNO) as NO donor, and the negative treatment (NT) solution containing 5 μmol L−1 carboxy-PTIO (c-PTIO, NO scavenger), 200 μmol L−1 NG-Nitro-L-arginine methyl ester (L-NAME, NO synthase-like enzyme inhibitor), and 200 μmol L−1 sodium tungstate dihydrate (nitrate reductase inhibitor) and stored at 0°C. The results showed that NO decreased the activity of S-adenosylmethionine synthase and S-adenosylhomocysteine hydrolase and increased the activity of methionine sulfoxide reductase A, as well as the content of N5-methyl-THF, the ratio of tetrahydrofolate (THF), homocysteine, methionine, S-adenosylmethionine (SAM), and SAM to S-adenosylhomocysteine compared with the control, indicating that NO effectively increased FOCM flux by affecting the activity of FOCM enzymes. Meanwhile, NO increased the activities of H+-ATPase, Ca2+-ATPase, cytochrome c oxidase, succinate dehydrogenase, and the contents of adenosine triphosphate and adenosine diphosphate, and maintained high energy charge in peaches during storage. NO retarded the increase in mitochondrial permeability transition, reactive oxygen species content, and the decrease in mitochondrial membrane fluidity, membrane potential, and swelling. NT treatment exhibited the opposite results. In conclusion, these results suggested that NO could induce the accumulation of folate and FOCM flux and maintain mitochondrial energy levels, which might be responsible for maintaining the quality of peaches during cold storage.